Resistance to VAW global norms: The controversy surrounding marital rape in Ethiopia - Meron Zeleke Eresso (Danish Institute for International Studies (DIIS), 2021)
Marital rape and intimate partner violence are controversial issues all over the world either because they are recognised as criminal acts and strongly condemned, or because they are silenced as something that belongs to the private sphere and should not be the object of public scrutiny. In either case, they are acts of repression and gender inequality. In this DIIS Working Paper, Meron Zeleke, associate professor at the Addis Ababa University, explores the issue in an Ethiopian context. She takes a point of departure in historical debates and outlines the development of global and regional norms. The Maputo Protocol on the rights of women in Africa explicitly condemns marital rape. Ethiopia has recently ratified the protocol but has made a number of reservations including in relation to marital rape. The main part of the paper is constituted by an analysis of the ambiguous law reforms when it comes to marital rape in Ethiopia. This analysis points to several different explanations of the lack of criminalisation of marital rape, but suggests that the recent change of government may create space for addressing the issue again. The paper is part of the GLOW research programme.
Keywords: 330; Gewalt; Geschlechterdiskriminierung; Frauen; Soziale Norm; Grundrecht; Äthiopien